DESIGN AND MONITORING ROOM SECURITY WITH IMAGE CAPTURE BASED INTERNET OF THINGS (IOT) AND ARTIFICIAL INTELLIGENCE (AI) - Hendradyanto Putro, Ricky Hendradyanto Putro; Harianto, Bambang Bagus; Sudrajat, Sudrajat (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
A security system is a mechanism that eliminates fear, anxiety, and worry associated with leaving valuables behind, thus freeing a person from all risks. A security system for facial recognition or a person’s identity when entering a room that has valuable value is supplemented by a notification through a smartphone. With this system, it can make it easier and remind a person to supervise their valuables. So that the room can bemonitored based on the Internet of Things (IoT) in combination with Artificial Intelligence (AI) technology and notifications through the Telegram application. The method used to support the design of the security system with image capture is a descriptive quantitative method with a prototyping model. Prototyping is an approach method in which the initial model or prototype of the system to be developed is created and tested before full development begins. The results of the study show that room security systems based on the Internet of Things (IoT) and Artificial Intelligence (AI) can be done well. However, there are still some improvements and developments so that the design can be used or functioned optimally by users.